2019
DOI: 10.1103/physrevb.100.235145
|View full text |Cite
|
Sign up to set email alerts
|

Flat bands and nontrivial topological properties in an extended Lieb lattice

Abstract: We report the appearance of multiple numbers of completely flat band states in an extended Lieb lattice model in two dimensions with five atomic sites per unit cell. We also show that this edge-centered square lattice can host intriguing topologically nontrivial phases when intrinsic spinorbit (ISO) coupling is introduced in the microscopic description of the corresponding tight-binding Hamiltonian of the system. This ISO coupling strength acts like a complex next-nearest-neighbor hopping term for this model a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 87 publications
0
23
0
Order By: Relevance
“…Systems that exhibit flat-band physics correspond usually to specially "engineered" lattice structures such as quasi-1D lattices [6,17,18], diamond-type lattices [19], and so-called Lieb lattices, [7,[20][21][22][23][24]. Indeed, the Lieb lattice, a two-dimensional (2D) extension of a simple cubic lattice, was the first where the flat band structure was recognized and used to enhance magnetic effects in model studies [2, 25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systems that exhibit flat-band physics correspond usually to specially "engineered" lattice structures such as quasi-1D lattices [6,17,18], diamond-type lattices [19], and so-called Lieb lattices, [7,[20][21][22][23][24]. Indeed, the Lieb lattice, a two-dimensional (2D) extension of a simple cubic lattice, was the first where the flat band structure was recognized and used to enhance magnetic effects in model studies [2, 25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Most other flat-band systems cited above are also of the Lieb type and exists as either 2D, quasi-1D or 1D lattices [27]. Less attention has been given to 3D flat-band systems [19] or extended Lieb lattices [24,28]. Furthermore, while disorder in quasi-1D [29][30][31][32] and 2D [33] has previously received some attention, comparatively little work has investigated the influence of disorder on 3D flat-band systems [17,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…sHCL was first studied more than two decades ago in the context of electronic systems [95,115]. Recently Dirac cones and conical diffraction in such superlattices were also theoretically investigated [104,116,117] in cold atoms and optics, but experimental study is lacking because of the difficulty in constructing such sophisticated lattices. sHCL has five lattice sites (a-e) per unit cell, as shown in Figure 7A, and its tight-binding band structure consists of five bands, including a completely flatband touching two dispersive conical bands at the center (Γ point) of the first BZ, which resembles the pseudospin-1 Dirac cone in the Lieb lattice.…”
Section: Line States In Lieb and Superhoneycomb Latticesmentioning
confidence: 99%
“…This is equivalent to effectively having zero kinetic energy in these bands and hence to promoting the remaining terms in the Hamiltonian such as potential and interaction terms. Usually, such flat bands emerge only for specially "engineered" lattice structures such as quasi-1D lattices [13][14][15], diamond-type lattices [16], and Lieb lattices [17][18][19][20][21][22]. Lieb lattices were originally used to enhance magnetic effects in model studies [9,23,24] but have now been shown to be of experimental relevance in Wigner crystals [12], high-temperature superconductivity [10,18], photonic wave guide arrays [8,[25][26][27][28], Bose-Einstein condensates [29,30], ultra-cold atoms in optical lattices [31] and electronic systems [32].…”
Section: Introductionmentioning
confidence: 99%